Vigor control in ’Abate Fetel’ pear by root pruning - Würz, Douglas André; Gonçalves, Mayra; Daboit, Rafael; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2019)
The objective of this work was to evaluate the effect of different levels of root pruning on the vegetative growth, yield and quality of fruits of ‘Abate Fetel’ pear. The experiment was conducted during the cropping seasons of 2007 and 2008. The treatments consisted of: root pruning at 20 cm of the plant, 35 cm and control without root pruning. Root pruning showed vigor control and maintenance of vegetative characteristics, however, it did not influence the productive and physical-chemical indices of the fruits. It is concluded that root pruning promotes vigor control in ‘Abate Fetel’ pears.